Poly(2-ethyl-2-oxazoline) as Alternative for the Stealth Polymer Poly(ethylene glycol): Comparison of in vitro Cytotoxicity and Hemocompatibility - Bauer, Marius; Lautenschlaeger, Christian; Kempe, Kristian; Tauhardt, Lutz; Schubert, Ulrich S.; Fischer, Dagmar (Macromolecular Bioscience, 2012)
Limitations of PEG in drug delivery have been reported from clinical trials. PEtOx (0.4-40kDa) as alternative is synthesized by a living, microwave-assisted polymerization, and is directly compared to PEG of similar molar mass regarding cytotoxicity and hemocompatibility. In short-term treatments, both types of polymers are well tolerated even at high concentrations. Moderate concentration and molar mass dependent cytotoxic effects occurred only after long-term incubation at concentrations higher than therapeutic doses. PEtOx possesses not only an easy route of synthesis and beneficial physicochemical characteristics such as low viscosity and high stability, which are advantageous over PEG, but additionally in vitro toxicology comparable to PEG. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biocompatibility; Hydrophilic polymers; Poly(2-oxazoline)s; Poly(ethylene glycol)s; Stealth effect